Unconcealed, the international network of conceptual artists 1967-77 : dealers, exhibitions and public collections - Richard, Sophie; Morris, Lynda; Norwich University College of the Arts. (London : Ridinghouse, 2009)
"Unconcealed" describes the emergence of Conceptual art in Europe through the growth of an international network of artists, dealers, museum curators, collectors and critics. The publication is a detailed account of the decade 1967-77. The relationships, support structures and strategies of dealer galleries such as Konrad Fischer, Wide White Space and Lisson Gallery to promote artists such as Marcel Broodthaers, Richard Long and Lawrence Weiner, are revealed. The central section of the book brings to life many of the important figures of the art world of this period with a selection of Jacques Charlier's Vernissage des Expositions photographs from 1974-75 that were first shown at the Palais des Beaux-Arts, Brussels in 1975. Previously unpublished data recording the exhibitions and sales of Conceptual artworks to galleries, public institutions and private collections is a major feature of the book. For example, Richard has gathered data from the archives of leading European museums, charting purchases of international artists from dealers to museums, highlighting the power of these relationships. Some of the databases reveal a correlation between temporary exhibitions and museum purchases, suggesting that we need to consider the role of 'dealer-curators' as prime protagonists of this period. Richard's also conducted interviews with dealers, curators, artists and collectors of the period which further highlights the importance of the relationships brought to light in Unconcealed"--Publisher's website
"Produced in association with Norwich University College of the Arts."
Includes bibliographical references (p. 490-499) and index.
boek